Assessment of technological pollution sources influence on underground water on the territory of Kharkiv region - Прибилова, В. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. To date, a large number of environmental problems remain unsolved.Moreover, their number increases year after year. First of all, this is due to the impact of man on a balanced nature, the expansion of industrial and agricultural production. Kharkiv region, whose industry plays a significant role in Ukraine's production and gives a tenth of all industrial production in the country, was investigated in the article to assess the impact of technogenic sources of groundwater contamination. There are more than 1200 industrial enterprises located here, indicating an extremely high level of industrialization, which results in the formation of significant volumes of industrial waste and negatively affects the environment. Powerful heavy industry enterprises on the territory of Kharkiv region, which have worn-out and technically outdated workshops and production in their structure, produce large volumes of industrial waste, which, in turn, causes an unfavorable environmental condition in the cities of the region, such as chemical pollution of air, soils, groundwater.The purpose of the article is to assess the impact of technogenic sources of groundwater pollution on the territory of Kharkiv region.Presenting main material. The article gives a description of the influence of the most significant objects of Kharkiv region, which pose a possible threat to groundwater, and therefore to the water intakes they operate. The sources of concentrated groundwater contamination in the investigated area are mainly large industrial enterprises, which, by their nature, use water in significant volumes and, as a result, have large amounts of waste water. Such sites are on the territory involved in the production cycle. These are septic tanks, sludges, heat exchangers, quarries, access platforms, warehouses, burial sites of various wastes, etc.Conclusions. Several significant sites are located on the territory of Kharkiv region, which pose a possible threat to underground waters, and therefore to water intakes that operate them. These are, first of all, Zmiiv heat-station, Pervomaisky "Khimprom", Balakliya cement-slate intergated works, "Shebelinka gas-extraction", the point of radioactive waste disposal in the village of Dergachi, Dergachi District Solid Waste Management and some other active industrial enterprises.Based on the data of groundwater aquifers’ chemical composition in the zone of influence of technogenic sources for the long period of observations, appropriate conclusions were drawn regarding pollution.